Visualization of Flow Field: Application of PLIF Technique - Jiang Bo Peng; Ze Fang Lv; Xin Yu; Song He Meng; Hao Dong; Fan Deng; Lin Chen; De Ying Chen; Rong Wei Fan; Zhi Wei Dong; Xu Dong Li (Journal of Spectroscopy)
The objective of this paper is to apply planar laser-induced fluorescence (PLIF) technology to flow field visualization. This experiment was carried out in a one-meter wind tunnel to study the wake flow field around a circular cylinder. This experiment studied the method of injecting tracer into the flow field; the frequency of the vortex in the wake field and the vortex speed are quantitatively analyzed. This paper gives the correspondence between the speed of the flow field and the frequency of the laser, which could be used as a rough reference standard for future wind tunnel visualization experiments. The result shows that PLIF diagnostic technology has great potential in visualization of flow field.